Synthesis of optimal structure of the observer of the initial condition of multidimensional object with any dynamics at random influences - Білак, Н. В.; Польова, А. М.; Юзич, Н. А. (Problems of Informatization and Control, 2014)
Procedure of synthesis of optimal structure of the observer of the initial condition of multidimensional object with any dynamics at random influences is offered. It is provided the solution version of the task by division of object into 2 parts (stable and unstable channels), for each of them two observers of the initial condition of multidimensional object are under construction separately